Spatio-Temporal Variations of the PM2.5/PM10 Ratios and Its Application to Air Pollution Type Classification in China - Fan, Hao; Zhao, Chuanfeng; Yang, Yikun; Yang, Xingchuan (Frontiers in Environmental Science, 2021)
Particulate Matter (PM) is an important indicator of the degree of air pollution. The PM type and the ratio of coarse and fine PM particles determine the ability to affect human health and atmospheric processes. Using the observation data across the country from 2015 to 2018, this study investigates the distribution and proportion of fine particles (PM2.5) and total particles (PM10) at different temporal and spatial scales in mainland China; clarifies the PM2.5, PM10 and PM2.5/PM10 ratios interrelation; and classifies the dust, mixed, and anthropogenic type aerosol. It shows that the annual average concentration of PM2.5 and PM10 decreased by 10.55 μg m-3 and 8.78 μg m-3 in 4 years. PM2.5, PM10, and PM2.5/PM10 ratios show obvious while different seasonal variations. PM2.5 is high in winter and low in summer, while PM10 is high in winter and spring, and low in summer and autumn. Differently, the PM2.5/PM10 ratios are the highest in winter, and the lowest in spring. PM2.5/PM10 ratios show strong independence on PM2.5 and PM10, implying that it can provide extra information about the aerosol pollution such as aerosol type. A classification method about air pollution types is then further proposed based on probability distribution function (PDF) morphology of PM2.5/PM10 ratios. The results show that dust type mainly lies in the west of Hu-Line, mixed type pollution distributes near Hu-Line, and the anthropogenic type dominates over North China Plain and cities in southern China. The results provide insights into China’s future clean air policy making and environmental research.